Perbandingan Penggunaan Bahasa Inggris dalam Dokumentasi Elektronik dan Manual dalam Praktek Keperawatan - Rudi Purwana; Mariana Mariana (Pusat Riset dan Inovasi Nasional, 2021)
This research aims to evaluate the differences in the use of the English language in electronic and manual documentation in nursing practice. Documentation is a crucial element in patient care, and with technological advancements, many healthcare institutions are transitioning from manual records to electronic documentation systems. The focus of this study is to identify variations in clarity, accuracy, and efficiency of nurse communication using both documentation methods.The research methodology involves surveys and document analysis on a sample of nurses engaged in both types of documentation. Surveys will assess nurses' perceptions regarding the clarity of documented information, the accuracy of information, and the efficiency of usage. The analyzed documents will include patient records, care plans, and incident reports.The research outcomes are expected to provide insights into the strengths and weaknesses of each documentation method, aiding healthcare organizations in decision-making regarding the implementation or development of documentation systems. The practical implications of this research can enhance nurse communication effectiveness and the quality of patient care, especially in the continually evolving healthcare information technology era.